Relationship between Social Media Use with teenager Physical, Mental and Social Health - Sevilla Ukhtil Huvaid; Erni Maywita (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2022)
Teenagers as users of social media are not very able to sort out which information and communication can be of benefit to them. They also tend to be easily influenced by the social environment without first considering what positive or negative impacts they will receive. The presence of social media certainly has a huge influence on people's lives, including teenagers, but of course there will be positive and negative impacts on its use, including on the health aspect. The purpose of this study was to determine the impact of social use on teenagerhealth. This research is a type of quantitative research with a cross-sectional research design which was conducted at Gunung Talang 1st Public Vocational Secondary Schools, Solok Regency in 2019. The study population totaled 44 people and all populations were used as samples. Data analysis was performed using the Chi-Square test. The results of the univariate analysis showed that almost all teenagers (72.7%) had poor health and more than half of teenagers (56.8%) had high intensity use of social media. Based on the results of the bivariate analysis it is known that there is a relationship between the use of social media and teenagerhealth where a p-value of 0.031 is obtained. Therefore, there is a need for further coordination between parents and the school in supervising the use of social media by teenagers in order to prevent things that are negative. Parents should also increase controls to ensure that their teens use social media in a positive way. Keywords: Adolescent, Health, Mental, Physical, Social Media